2022
DOI: 10.1002/cne.25326
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of prototypical primary cilia markers in subtypes of retinal ganglion cells

Abstract: Loss of retinal ganglion cells (RGCs) underlies several forms of retinal disease including glaucomatous optic neuropathy, a leading cause of irreversible blindness. Several rare genetic disorders associated with cilia dysfunction have retinal degeneration as a clinical hallmark. Much of the focus of ciliopathy associated blindness is on the connecting cilium of photoreceptors; however, RGCs also possess primary cilia. It is unclear what roles RGC cilia play, what proteins and signaling machinery localize to RG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 80 publications
(111 reference statements)
3
8
1
Order By: Relevance
“…Since little is known regarding cilia in nonphotoreceptor cells in retinal organoids [46,52], we focused our analysis on the inner retina during organoid development. Consistent with our previous reports in mouse retinas [31,45], many ciliated cells (excluding photoreceptors) appeared in the inner parts of retinal organoids at all developmental time points (Figure 1(a)). Next, we assessed the number of cells (excluding photoreceptors) with cilia (ciliation) at different retinal organoid developmental stages.…”
Section: Primary Cilia Are Expressed In the Inner Part Of Hesc-derive...supporting
confidence: 92%
See 4 more Smart Citations
“…Since little is known regarding cilia in nonphotoreceptor cells in retinal organoids [46,52], we focused our analysis on the inner retina during organoid development. Consistent with our previous reports in mouse retinas [31,45], many ciliated cells (excluding photoreceptors) appeared in the inner parts of retinal organoids at all developmental time points (Figure 1(a)). Next, we assessed the number of cells (excluding photoreceptors) with cilia (ciliation) at different retinal organoid developmental stages.…”
Section: Primary Cilia Are Expressed In the Inner Part Of Hesc-derive...supporting
confidence: 92%
“…AP2α-positive amacrine cells in retinal organoids demonstrated primary cilia at all developmental stages, from day 44 to day 176 (Figure 4(a)). Quantitative analysis showed that the frequency (ciliation) and length of primary cilia displayed no We and others have previously reported the presence of primary cilia within RGCs and their subtypes in mice and zebrafish [25,45]. In this study, our efforts focused on characterizing the frequency and length of primary cilia during the development and differentiation of Brn3b-positive RGCs in retinal organoids.…”
Section: Primary Cilia Are Present and Stable In Ap2α-positivementioning
confidence: 93%
See 3 more Smart Citations